Development of Logic Gate Trainer Kit Media: Validity Study - Syaiful, M (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study aims to develop a Logic Gate Trainer Kit as an effective instructional medium and to evaluate its validity through expert assessment. The development process adopts the Instructional Development Institute (IDI) model, which consists of three stages: define, develop, and evaluate. During the define phase, instructional needs and media specifications were identified. In the develop phase, a prototype of the trainer kit was created based on the instructional objectives and technical requirements. The evaluate phase involved expert validation to assess the media’s quality and relevance. A total of four media experts and four subject matter experts participated in the validation process. The results of the media expert validation yielded an average score of 0.78 %, exceeding the minimum validity threshold of 0.667 %, indicating that the media is valid. Similarly, the validation by subject matter experts produced an average score of 0.82%, confirming the content validity of the trainer kit. These findings demonstrate that the Logic Gate Trainer Kit is a valid learning medium and suitable for use in digital electronics instruction.